2007
DOI: 10.1158/1078-0432.ccr-06-2446
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance Proteins Do Not Predict Benefit of Adjuvant Chemotherapy in Patients with Completely Resected Non–Small Cell Lung Cancer: International Adjuvant Lung Cancer Trial Biologic Program

Abstract: Purpose: The purpose of our study was to determine whether multidrug resistance proteins (MRP) are of prognostic and/or predictive value in patients who were enrolled into the International Adjuvant Lung CancerTrial (IALT). Experimental Design: Expression of MRP1and MRP2 was immunohistochemically assessed in tumor specimens obtained from 782 IALT patients. Prognostic and predictive analyses were based on Cox models adjusted for clinical and pathologic variables. Results: MRP1expression was considered positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 20 publications
5
33
1
2
Order By: Relevance
“…Filipits et al (18) found that NSCLC patients suitable for surgery had a positive MRP1 expression rate of 47% and a positive MRP2 expression of 40%. The overall survival rates of NSCLC patients with a positive MRP2 expression were markedly shorter compared with those of patients with a negative MRP2 expression (P=0.007), suggesting that MRP2 protein expression may be an indicator of poor prognosis of NSCLC patients suitable for surgery.…”
Section: Surgerymentioning
confidence: 99%
“…Filipits et al (18) found that NSCLC patients suitable for surgery had a positive MRP1 expression rate of 47% and a positive MRP2 expression of 40%. The overall survival rates of NSCLC patients with a positive MRP2 expression were markedly shorter compared with those of patients with a negative MRP2 expression (P=0.007), suggesting that MRP2 protein expression may be an indicator of poor prognosis of NSCLC patients suitable for surgery.…”
Section: Surgerymentioning
confidence: 99%
“…Multicenter clinical trails with larger sample size, such as the International Adjuvant Lung Cancer Trial biologic Program (IALT-bio) and the Lung Adjuvant Cisplatin Evaluation biologic Program (LACE-Bio) (25)(26)(27), should be conducted for the application of ERCC1 in clinic. Nevertheless, studies on biomarkers like ERCC1 provides an onset for overcoming drug resistance and tailoring chemotherapy in NSCLC treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of ABCC1 has been described in NSCLC (19). No positivity was seen for ABCC1 in the tumor presenting the EGFR mutation despite being present in four other adenocarcinomas not bearing the mutation.…”
Section: Discussionmentioning
confidence: 96%